Changes in the prevalence of physical inactivity and sedentary behavior during COVID-19 pandemic: a survey with 39,693 Brazilian adults - Silva,Danilo Rodrigues Pereira da (2021)
Abstract: This study analyzed changes in the prevalence of physical inactivity and sedentary behaviors according to correlates during the COVID-19 pandemic among Brazilian adults. A national retrospective online survey was conducted with 39,693 Brazilian adults. Physical activity (weekly frequency and daily duration; cut-off point of 150 minutes/week), TV-viewing time and computer/tablet use (daily duration; cut-off point of 4 hours/day) before and during the pandemic period were reported. Sex, age group, schooling level, skin color, per capita income, country region, working status during the quarantine, and adherence to the quarantine were the correlates. Descriptive statistics were used. The prevalence of physical inactivity, high TV-viewing time and computer/tablet use increased, respectively, 26%, 266%, and 38% during the pandemic. While increases in physical inactivity and computer/tablet were more widespread, higher increases in the prevalence of high TV viewing tiem were observed among younger adults (660%), with higher schooling level (437%) and those who were at home office (331%). The prevalence of physical inactivity and sedentary behaviors increased in all population sub-groups during the COVID-19 pandemic in Brazil.